2022
DOI: 10.1007/s00500-022-07527-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary game analysis of enterprise carbon emission regulation based on prospect theory

Abstract: Aiming at the problem that the government regulates the carbon emission of enterprises, this paper introduces the prospect theory to correct the revenue function of government and enterprise, considering the risk of air quality deterioration, built an evolutionary game model of government and enterprise based on prospect theory.According to the weight of the two sides on the probability of air quality deterioration under the equilibrium state, the risk of air quality deterioration is divided into three levels:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…built an evolutionary game model of the government, contractors, and the public to study the problem of project quality supervision. Sun et al (2022) constructed an evolutionary game model based on prospect theory to study carbon emission regulation. Xia et (al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…built an evolutionary game model of the government, contractors, and the public to study the problem of project quality supervision. Sun et al (2022) constructed an evolutionary game model based on prospect theory to study carbon emission regulation. Xia et (al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of carbon emission reduction, Zhang et al [45] used the two-party evolutionary game model of prospect theory to study the interactive relationship between local governments and port enterprises in the context of green port construction. Sun et al [46] established an evolutionary game model between the government and enterprises based on prospect theory. This study considered the strategic choices of the government and enterprises under different risk levels of air quality deterioration, and found that under low-risk conditions, the government tends to adopt passive supervision.…”
Section: Research On Prospect Theorymentioning
confidence: 99%
“…Yang et al (2021) built an evolutionary game model of the government, contractors, and the public to study the problem of project quality supervision. Sun et al (2022) constructed an evolutionary game model based on prospect theory to study carbon emission regulation. Xia et (al.…”
Section: Literature Reviewmentioning
confidence: 99%